Petabencana.id in Flood Disaster Management: An Innovation in Collaborative Governance-based Early Warning System in Indonesia - Hidayat, Hisyam Yusril (Magister Administrasi Publik, 2020)
The flood disaster has become one of the most damaging hydro-meteorological disasters which recorded a loss of Rp30 trillion in Indonesia. The flood disaster early warning system is one of the most important parts of the disaster management process which can reduce the possibility of losses that can occur. The mandate of the existing regulation emphasizes that in the disaster early warning system it needs to involve various parties from public and nonpublic actors collaboratively. The manifestation of the mandate is Petabencana.id which was initiated by the Yayasan Peta Bencana and involved elements of government, universities, mass media, donor agencies, nonprofit organizations, and the community. This study analyzed the collaborative process of public and nonpublic actors through collaborative governance frameworks. This study included descriptive qualitative research with post-positivist paradigm and uses in-depth interview methods and directed content approach. Based on the findings, it is illustrated that the process of collaboration has been formed between the public and nonpublic actors. In terms of collaboration process, there is lack of transparency in Petabencana.id management especially in finance issue. The findings also revealed that the socialization process of Petabencana.id in community and educational entities still in effective and the roles of government role can be enforced. However, there is lack of role from the private sector which can contribute to make Petabencana.id better. This study still has limitation include the amount of informant of various elements from university, mass media, and community, in this study just use directed content approach to describe the perspectives of them in terms of collaboration process.Â